Websites continuance usage intention: a study from the airline sector - Khan, H. (Inderscience Publishers, 2023)
Airline websites aim to provide comprehensive and timely information to customers through the adoption and use of information management. Despite rapid growth in information systems (IS) research and practice, few literature reviews had addressed the problems of low cost airlines website quality. This empirical research paper draws constructs from the expectation confirmation model (ECM) and IS continuance literature to develop a better theoretical explanation for low-level airline websites' problem. The IS continuance research finds the substantive differences in construct between initial IS use and IS continuance over time. This paper has constructed a new research model for customers' continuance usage of airline websites and has empirically tested it using the structural equation modelling (SEM) approach. A survey instrument was used to acquire responses from 253 usable samples from respondents. SEM results indicated that the model constructs explained 55 of the variance in airline websites continuance. Â© 2023 Inderscience Enterprises Ltd.